Cuando ser autónomo no es suficiente: análisis de la autonomía municipal frente al marco legal establecido para el despliegue de la infraestructura de telecomunicaciones - De la Vega Pazos, Noelia Milagros (Pontificia Universidad Católica del Perú, 2025)
In this article we will analyze the concept of municipal autonomy in order to establish whether a government (local or regional) could issue a norm that regulates the display of the needed infrastructure to provide the services of telecommunications or if in any case, this is a contravention of the legal framework provided at a national level by Law No. 29022 and its complementary norms. Likewise, we will resort to pronouncements of the Constitutional Court to analyze the limits of municipal autonomy and we will seek to determine whether this may be sufficient grounds to apply an ordinance over a norm of national scope. Finally, we will present pronouncements of the Supreme Court that address the problem, in order to determine what is the position in the face of a possible antonymy of two norms with the same rank.

Por medio del presente analizaremos el concepto de la autonomía municipal, esto a modo de determinar si un gobierno (local o regional) podría emitir una norma que regule el despliegue para la infraestructura necesaria para brindar el servicio de telecomunicaciones o si en todo caso, ello resulta una contravención al marco legal establecido a nivel nacional mediante la Ley Nro. 29022 y sus normas complementarias. De igual manera, recurriremos a pronunciamientos del Tribunal Constitucional para contemplar los límites de la autonomía municipal y buscaremos determinar si esta puede ser causal suficiente para aplicar una ordenanza sobre una norma de alcance nacional. Finalmente, se presentarán pronunciamientos de la Corte Suprema que abordan la problemática abordada, para determinar cuál es la postura frente a una posible antinomia de dos normas con el mismo rango.
When being autonomous is not enough: analysis of municipal autonomy with respect to the legal framework established for the deployment of telecommunication infrastructure
Keywords: Municipal autonomy; Legal framework; National plan; Telecommunications; Limits; Autonomía municipal; Marco legal; Plan nacional; Telecomunicaciones; Límites; https://purl.org/pe-repo/ocde/ford#5.05.00